Particularities of Chronic Urticaria in Latin American Countries: Epidemiology, Pathogenesis and Treatment (2025)
ABSTRACT: Purpose of Review Chronic Urticaria is a multifactorial disease. Despite international guideline recommendations each region has particular characteristics with unique needs. The aim of this review is to present the particularities of urticaria in Latin America (LATAM) and evaluate the clinical and investigation costs of CSU in LATAM and other regions. Recent Findings In the last 10 years there has been a signifcant increase in research on CSU in LATAM. At the molecular level, the presence of specifc IgE against environmental allergens and eosinophils seems to be more frequent among CSU in LATAM than in other regions, suggesting a greater presence of type 2 infammation, perhaps secondary to the characteristics of the environment in some areas of LATAM. At a clinical level, there are common points and diferences with respect to what has been published in other regions, especially in terms of management secondary to economic access barriers. Summary It is important to understand the causes of these particularities to modify those that result in a high cost for the patient and society.